Tumor susceptibility gene 101 is required for the maintenance of uterine epithelial cells during embryo implantation - Hyunji Byun; Sojung Kwon; Kay-Uwe Wagner; Hyejin Shin; Hyunjung Jade Lim (BMC, 2021)
Abstract Background The tumor susceptibility gene 101 (Tsg101), a component of the endosomal sorting complex required for transport (ESCRT) complex I, is involved in multiple biological processes involving endomembranous structures and the plasma membrane. The role of Tsg101 in the uterine epithelium was investigated in Tsg101 floxed mice crossed with Lactoferrin-iCre mice (Tsg101 d/d ). Methods Tsg101 d/d mice were bred with stud male mice and the status of pregnancy was examined on days 4 and 6. Histological analyses were performed to examine the uterine architecture. Immunofluorescence staining of several markers was examined by confocal microscopy. Uterine epithelial cells (UECs) were isolated from Tsg101 f/f and Tsg101 d/d mice, and the expression of necroptosis effectors was examined by RT-PCR, western blotting, and immunofluorescence staining. UECs were also subjected to RNA expression profiling. Results Tsg101 d/d female mice were subfertile with implantation failure, showing unattached blastocysts on day 6 of pregnancy. Histological and marker analyses revealed that some Tsg101 d/d day 4 pregnant uteri showed a disintegrated uterine epithelial structure. Tsg101 d/d UECs began to degenerate within 18 h of culture. In UECs, expression of necroptosis effectors, such as RIPK1, RIPK3, and MLKL were first confirmed. UECs responded to a stimulus to activate necroptosis and showed increased cell death. Conclusions Tsg101 deficiency in the uterine epithelium causes implantation failure, which may be caused by epithelial defects. This study provides evidence that UECs harbor a necroptotic machinery that responds to death-inducing signals. Thus, Tsg101 expression in the uterine epithelium is required for normal pregnancy in mice.